Research Paper Writing and 'Peer Review': An Over View - Ekram, ARM Saifuddin; Rahman, Md Fazlur (TAJ: Journal of Teachers Association, 2009)
A research paper presents the results of investigations on a selected topic. Based on researchers own thoughts and the facts and ideas they have gathered from a variety of sources, a research paper is a creation that is usually unique. In Bangladesh about 100 science and research journals are published annually in English language of which 45 are biomedical journals. Most of these do not reach their target readers and are not indexed or abstracted. Amongst many other deterrents, poor peer review is one of the most important hindrance to quality publication of science journals regularly. For quality publication, journals need careful and consistent editing. A well prepared systematic and organized manuscript is a prerequisite for this purpose. Critical but sensible peer review can enhance and enrich the whole process. The final outcome will be a journal with sound science that can play its proper role in the development of the country. doi: 10.3329/taj.v15i2.3920 TAJ December 2002; Vol.15(2): 98-102